Digital Translation and Vocabulary Acquisition: Insights from Process-Oriented ELT Research - Nurul Widiatul Ihsan; Alda Dea Andani; Nur Aziza; Alfa Siti Sabilla; Glorya Olviana Sinaga; Refika Andriani (PROJECT (Professional Journal of English Education), 2026)
Vocabulary development in digitally mediated language learning remains a key challenge in contemporary English Language Teaching (ELT), particularly in understanding how learning actually occurs beyond measurable outcomes. Although translation and digital tools have been widely recognized for their pedagogical potential, little is known about the processes through which learners construct vocabulary knowledge during translation activities. Addressing this gap, this study investigates both the outcomes and processes of vocabulary acquisition through digital translation tasks. A sequential explanatory mixed-methods design was employed, involving pre-test and post-test to measure learners’ gains in environmental terminology, alongside screen recording analysis to capture real-time translation behaviors. The findings indicate significant improvement in learners’ vocabulary knowledge, accompanied by active engagement in searching, verifying, and refining lexical items. More importantly, vocabulary learning was found to occur through iterative and non-linear processes, reflecting learners’ strategic interaction with digital resources. This study highlights the role of translation as a dynamic meaning-making activity rather than a product-oriented task. The findings contribute to ELT by providing process-oriented evidence of vocabulary learning and underscore the importance of integrating translation-based tasks and digital research skills to foster deeper learning, learner autonomy, and critical engagement in digitally mediated classrooms.